Fibrinogen and D Dimer in Healthy Nigerian Women on Hormonal Contraceptives - Abubakar, Sani Bako; Mamman, Aisha Indo; Abdul, Muhammad Adogie; Sabitu, Muhammad Zainu (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Hormonal contraceptives have been associated with increased tendency of thromboembolic disorders. However, a balance between fibrin generation and fibrinolytic activity has been shown to minimize the risk. The aim of the study was to assess the serum fibrinogen and D-Dimer level in hormonal contraceptives users. Methods: A total of 160 consenting participants made of 80 subjects on different forms of hormonal contraceptives and 80 controls on non hormonal IUCD were recruited into this study. A structured questionnaire was administered to obtain information required; blood samples were collected from each of the participant into appropriate containers using standard methods. Fibrinogen assay was done using the STAGO STart®4 coagulation analyzer while D-dimer was measured using ZYMUTEST DDIMER ELISA kit (HYPHEN BioMed). The results were analyzed using SPSS version 17.0 software. Statistical significance was based on p value < 0.05. Results. The mean fibrinogen levels of the study group and controls were 387.10±62.52 and 276.85±52.70 respectively, (reference range 180-400ng/ml). The mean D dimer concentrations of the study group was markedly elevated 813.36±212.35 while that of the controls was 257.04±108.33 (reference range <400). Both analytes showed a statistically significant difference between the study group and control (P<0.05). None of the client on COCP has elevated D dimer level. Conclusion: The significant increase in the procoagulant protein- fibrinogen and corresponding increase in fibrinolytic activity as demonstrated by elevated Ddimer level reflect a balance between fibrin formation and degradation hence minimizing the VTE risk. This balance is less prominent with use of COCP and can be attributed to the oestrogen component.